2024
DOI: 10.3390/antibiotics13020154
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimicrobial Approaches to Combat Bacterial Biofilms Associated with Urinary Tract Infections

Giuseppe Mancuso,
Marilena Trinchera,
Angelina Midiri
et al.

Abstract: Urinary tract infections (UTIs) are prevalent bacterial infections in both community and healthcare settings. They account for approximately 40% of all bacterial infections and require around 15% of all antibiotic prescriptions. Although antibiotics have traditionally been used to treat UTIs for several decades, the significant increase in antibiotic resistance in recent years has made many previously effective treatments ineffective. Biofilm on medical equipment in healthcare settings creates a reservoir of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 129 publications
1
1
0
Order By: Relevance
“…Neurological disorders were the only comorbidities that occurred more frequently in the study group compared to the control group. The fact that patients in both groups had a high rate of urosepsis on admission, as in other studies [37], demonstrates the aggressiveness of MDR Kpn. However, mortality was lower, demonstrating the better prognosis of urosepsis of urinary origin.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Neurological disorders were the only comorbidities that occurred more frequently in the study group compared to the control group. The fact that patients in both groups had a high rate of urosepsis on admission, as in other studies [37], demonstrates the aggressiveness of MDR Kpn. However, mortality was lower, demonstrating the better prognosis of urosepsis of urinary origin.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies have demonstrated bacterial colonization of catheters, including with Kpn through its ability to bind to biotic and abiotic surfaces via fimbriae [43]. After fixation, the germs form a bacterial biofilm [26,29,37,44], an element of bacterial persistence and the development of resistance to carbapenems [27]. We have shown that not only does the presence of Foley urethral catheters confer a risk of urinary tract infection with CR Kpn [6], but also the presence of double-J ureteral catheters, nephrostomy, cystostomy, or ureterostomy double-J catheters, as in other studies [26,27,29].…”
Section: Discussionmentioning
confidence: 99%